Children with Mental Illness and Their Families: Problems and Implications for Social Work - Nguyen Trung Hai; Vu Thuy Ngoc (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
This paper aims to assess the situation of children’s mental health as well as the problems that their families are facing. The results show that, currently, children in the study are facing many types of mental illness with different levels from light to serious mental health problems. Attention deficit hyperactivity disorder is the highest rate among mental health types. The causes of mental illness are quite diverse, including psychological and social causes. With such a situation, their families are also facing different issues and difficulties such as stress in the family; economic decline; being discriminated against; lack of childcare knowledge. Based on the study findings on the child mental health situation and the problems encountered by the family, the article has provided some information and discussions about solutions in general as well as emphasized on the implications of social work in intervening and supporting the problems that the research has discovered. Received 4th August 2023; Revised 20th August 2023; Accepted 12th September 2023